RANKL expression is differentially modulated by TLR2 and TLR4 signaling in fibroblasts and osteoblasts - Leite, Fabio Renato Manzolli [UNESP]; Aquino, Sabrina Garcia de [UNESP]; Guimarães, Morgana Rodrigues [UNESP]; Cirelli, Joni Augusto [UNESP]; Rossa Junior, Carlos [UNESP] (Herbert Publications, 2014)
Resident, non-immune cells express various pattern-recognition receptors and produce inflammatory cytokines in response to microbial antigens, during the innate immune response. Alveolar bone resorption is the hallmark of destructive periodontitis and it is caused by the host response to bacteria and their mediators present on the biofilm. The balance between the expression levels of receptor activator of nuclear factorkappa B ligand (RANKL) and osteoprotegerin (OPG) is pivotal for osteoclast differentiation and activity and has been implicated in the progression of bone loss in periodontitis. To assess the contribution of resident cells to the bone resorption mediated by innate immune signaling, we stimulated fibroblasts and osteoblastic cells with LPS from. Escherichia coli (TLR4 agonist), Porphyromonas gingivalis (TLR2 and -4 agonist), and interleukin-1 beta (as a control for cytokine signaling through Toll/IL-1receptor domain) in time-response experiments. Expression of RANKL and OPG mRNA was studied by RT-PCR, whereas the production of RANKL protein and the activation of p38 MAPK and NF-kB signaling pathways were analyzed by western blot. We used biochemical inhibitors to assess the relative contribution of p38 MAPK and NF-kB signaling to the expression of RANKL and OPG induced by TLR2, -4 and IL1β in these cells. Both p38 MAPK and NFkB pathways were activated by these stimuli in fibroblasts and osteoblasts, but the kinetics of this activation varied in each cell type and with the nature of the stimulation. E. coli LPS was a stronger inducer of RANKL mRNA in fibroblasts, whereas LPS from P. gingivalis downregulated RANKL mRNA in periodontal ligament cells but increased its expression in osteoblasts. IL-1β induced RANKL in both cell types and without a marked effect on OPG expression. p38 MAPK was more relevant than NF-kB for the expression of RANKL and OPG in these cell types.
Keywords: Lipopolysaccharide; Porphyromonas gingivalis; Cell signaling; RANKL; OPG